Pengaruh Waktu Terhadap Intensitas Penyakit Blast Dan Keberadaan Spora Pyricularia Grisea (Cooke) Sacc.Pada Lahan Padi Sawah (Oryzae sativa) Di Kecamatan Samarinda Utara - Ni'matuljannah Akhsan; Pratiwi Jati Palupi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The objective of this study was to observe the effect of duration of infection on the blast intensity and the presence of Pyricularia grisea (Cooke) Sacc. spores on lowland rice (Oryzae sativa). The experiment was conducted in North Samarinda and also in the Laboratory of Plant Pests and Diseases Faculty of Agriculture, University of Mulawarman, from January up to April 2013. Survey method was used in lowland rice fields, observations were made on rice crops in three different fields. Each fields sample was taken eight observations are averaged from eight samples. The results showed that the rice leaf spot because of blast, the intensity of the blast and the number of spores of P. grisea ( Cooke ) Sacc. around the rice crop canopy Inpari 7, Cibogo and Ciherang was affected by the duration of infection. The longer the time available, the higher the intensity of the blast and the greater number of spores were trapped on all varieties tested.